A Large Isolated Congenital Left Circumflex Artery-to-Right Atrial Fistula in a 9-Year-Old Child - Li, Xin; An, Jun; Wang, Shuai; Lu, Wanli; Liu, Zhigang; Wu, Yili; Jiao, Fengjuan (Frontiers in Pediatrics, 2020)
Isolated congenital coronary artery fistula (ICCAF) is an exceedingly rare anomaly in which there is a direct abnormal connection between a coronary artery and other cardiac chambers or any of great vessels. The left circumflex artery (LCX) is the least common source of ICCAF. Here we reported a rare case of large ICCAF originated from the LCX in a 9-year-old boy. He presented fatigability, murmurs and NYHA class II. Echocardiography and cardiac CT revealed that an aneurysmal dilatation of the LCX along with the dilated coronary sinus entered into the right atrium (RA) through the great cardiac vein. However, it showed that the dilated LCX directly drained into the RA by coronary angiography, which was confirmed by the surgery. During the surgical procedure, the LCX fistula was identified in a 3*3 cm bulbous structure, the aneurysmal dilation of RA tissue. The end of fistula was located in the lower-middle interatrial septum, which was near the coronary sinus and above the opening of inferior vena cava (IVC). Transcardiac chamber closure with cardiopulmonary bypass (CPB) was successfully performed for the correction of the fistula. It indicated that preoperative angiography is essential to define the details of large ICCAF with aneurysmal dilation. Moreover, transcardiac chamber closure with CPB is the optimal procedure for the treatment of large ICCAF, while interventional catheterization is not feasible due to the presence of aneurysmal dilation of the LCX. The description of this rare case might have great value for the diagnosis and treatment of large ICCAF originated from the LCX.